(untitled) (Journal of the Bangladesh Agricultural University, 2012)
Lignosus bean is a perennial vine of Fabaceae. Green seeds, tender leaves and twigs are used as vegetable and dry split cotyledons as pulse soup. Canopy characters, growth and biochemical features of the two genotypes, G1 and G2, of Lignosus bean were studied. Numbers of leaf meter-1 vine, % fertile inflorescence plant-1, green pod yield plant-1 and dry mass plant-1 were greater in G1 genotype (10.11, 73.17%, 3.21 kg and 2.68 kg, respectively) than G2 genotype (9.55, 66.52%, 2.80 kg and 1.97 kg, respectively). On the other hand, leaflet area, inflorescence length, number of node and pod inflorescence-1, fresh pod length and width, hundred fresh seed weight and shell ratio were higher in G2 genotype (33.26 cm2 , 9.47 cm, 24.33, 3.51, 6.99 cm, 1.55 cm, 125.08 g, 83.61%, respectively) than that in the G1 one (29.04 cm2 , 0.61 cm, 8.32 cm, 16.0, 2.52, 6.56 cm, 1.35 cm, 80.57 g, 72.69%, respectively). Total soluble solids of seed; and total chlorophyll of leaf and seed were also higher in G2 (31.43%, 59.19 mg/l and 0.83 mg/l, respectively) but Vitamin C of green seed was higher in G1 genotype (43.84 mg%). It may be concluded that the two genotypes can be distinguished on the characters of leaf, flower and seed. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12038 J. Bangladesh Agril. Univ. 10(1): 4348, 2012